I'll never be French (no matter what I do) : living in a small village in Brittany - Greenside, Mark. (New York : Free Press, 2008)
Author and teacher Mark Greenside recounts his struggles to fit into the life of a small Celtic village in Brittany.
Keywords: Americans -- France -- Brittany; Country life -- France -- Brittany; Brittany (France) -- Description and travel; Brittany (France) -- Social life and customs